PENGARUH PENDAPATAN ASLI DAERAH, INDEKS PEMBANGUNAN MANUSIA DAN TENAGA KERJA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (38 Kabupaten/Kota di Provinsi Jawa Timur Tahun 2011-2016) - Asya Yandi Dea Kristina (Program Studi Ekonomi Pembangunan, 2017)
This research is aimed at finding the increase of authentic-local income, human development index, and labors in some cities/regencies in East Java. Further, this research is aimed at find out the influence of authentic-local income, human development index, and labors on the gross regional domestic product in some cities/regencies in East Java. In this research, the researcher used multiple regression as the research instrument with panel data during the period 2011-2016. This research used Fixed Effect Model as the research design. Based on the result of data analysis, it showed that the variable of authentic-local income positively and significantly influenced the coefficient equal to 38.25679, human development index negativ significantly influenced the coefficient equal to -514690.0, and labors significantly influenced the coefficient equal to 26.10263. Meanwhile, the determination coefficient (R2) was 0.99 or 99%. It indicated that the potentiality of authentic-local income, human development index, and labors in determining gross regional domestic bruto was 99%. Keywords: Gross Regional Domestic Bruto, Authentic-Local Income, Human Development Index, and Labor